Chemical Characterization and Microbiology of Khalas’s Date Vinegar (Phoenix dactylifera) - Devi Arianty; Nur Adawiyah Mahmud; Ernawati Ernawati (Universitas Sebelas Maret (UNS), 2024)
Date vinegar is a processed date product that has a high nutritional content that improves the function of the body’s work system. This research aims to identify the chemical characterization and microbiology of date vinegar as an antimicrobial during the fermentation process. This study used a descriptive method for 30 days of the fermentation of date vinegar. The results were analyzed by a qualitative description of each parameter. Parameters observed were characterization of date vinegar compared to standard fermented vinegar according to SNI 01-4371-1996, organic acids, total phenols, and antimicrobial effect. The results indicated that the fermentation of Khalas dates for 30 days produced a pH of 4, 7.15% dissolved solids, 0% alcohol, 6% acetic acid, organic acid odor, liquid form, and dark brown color. The bioactive content of date vinegar was obtained using GC-MS a total of 44 compounds with two highest peaks were detected at RT 21.68 and RT 22.08. The resulting compounds are hexadecenoic methyl ester, Pentadecanoic acid, 14-methyl-, methyl ester dan Pentadecanoic acid, 13-methyl-, methyl ester, area at 19.98. On the other peaks are l-(+)-Ascorbic acid 2,6-dihexadecanoate, Estra-1,3, 5 (10)- trien-17β-ol, area at 9.79. Total phenol was 6213.57 mg/L, and the highest antimicrobial activity was with a concentration of 100% date vinegar of 15.27 mm.